2006
DOI: 10.1097/00124645-200601000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Competencies for RNs in Hospitals

Abstract: Nurses in staff development are responsible for assuring nurses' competence in the delivery of care. Older patients are the predominant population in hospitals, yet there are no instruments that specifically assess the competency of nurses to deliver care to older patients. This article reports on the development and testing of an instrument, Geriatric Competencies for RNs in Hospitals, and makes recommendations as to how staff development educators can use the geriatric competency instrument with staff nurses. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…They found that the continuous education program increased the nurses’ knowledge about ageing and promoted more positive attitudes toward older people. The findings from this narrative literature review support Donahue et al’s27 study that geriatric education can improve knowledge and attitudes toward older people 28,29. In addition, the fact that there are no studies, which have examined either the attitudes of healthcare professionals in Saudi Arabia, or the potential knowledge gaps that these professionals may have, signifies the importance of continuing education for health professionals in the care of older people.…”
Section: Factors Affecting Knowledge and Attitudes Toward Older Peoplesupporting
confidence: 79%
“…They found that the continuous education program increased the nurses’ knowledge about ageing and promoted more positive attitudes toward older people. The findings from this narrative literature review support Donahue et al’s27 study that geriatric education can improve knowledge and attitudes toward older people 28,29. In addition, the fact that there are no studies, which have examined either the attitudes of healthcare professionals in Saudi Arabia, or the potential knowledge gaps that these professionals may have, signifies the importance of continuing education for health professionals in the care of older people.…”
Section: Factors Affecting Knowledge and Attitudes Toward Older Peoplesupporting
confidence: 79%
“…It is timely, given the ageing of the population, to undertake further intervention research so that the best evidence for dementia care practice and policy in acute settings is available. In addition, investigation into nurses' competence in the delivery of care to older people with dementia needs further exploration (Mezey et al 2006) so that management can select and appoint appropriately skilled staff to provide care that is both person centred and dementia specific. Finally, staff education and training is of prime importance, and in particular it must go beyond education of individuals to facilitate positive organisational change.…”
Section: Conclusion and Relevance To Clinical Practicementioning
confidence: 99%
“…Core competencies in the care of older adults including nutritional aspects of nursing care have been developed (Mezey, Quinlan, Fairchild, & Vezina, 2006) and can be utilized to assure competence for hospital nurses in caring for older adults. The Theory of Compromised Eating Behavior also emphasizes the need for basic nursing education to include nursing care relative to the general healthcare needs of the older adult population.…”
Section: Nursing Educationmentioning
confidence: 99%